FSHB Genotype Identified as a Relevant Diagnostic Parameter Revealed by Cluster Analysis of Men With Idiopathic Infertility - Krenz, Henrike; Sansone, Andrea; Kliesch, Sabine; Gromoll, Joerg; Schubert, Maria (Frontiers in Endocrinology, 2021)
Introduction and Objectives: Around 70% of infertile men are diagnosed with idiopathic infertility, thereby lacking major causative factors to explain their impaired fertility status. In this study, we used a large cohort of idiopathic infertile men to determine whether subgroups could be identified by an unbiased clustering approach and whether underlying etiologic factors could be delineated. Patients and Methods: From our in-house database Androbase, we retrospectively selected patients (from 2008 to 2018) with idiopathic male infertility (azoo- to normozoospermia) who fit the following selection criteria: FSH ≥ 1 IU/l, testosterone ≥ 8 nmol/l, ejaculate volume ≥ 1.5 ml. Patients with genetic abnormalities or partners with female factors were excluded. For the identified study population (n=2742), we used common andrologic features (somatic, semen and hormonal parameters, including the FSHB c.-211G>T (rs10835638) single nucleotide polymorphism) for subsequent analyses. Cluster analyses were performed for the entire study population and for two sub-cohorts, which were separated by total sperm count (TSC) thresholds: Cohort A (TSC  1 mill/ejalc; n=2422) and Cohort B (TSC < 1 mill/ejac; n=320). For clustering, the partitioning around medoids method was employed, and the quality was evaluated by average silhouette width. Results: The applied cluster approach for the whole study population yielded two separate clusters, which showed significantly different distributions in bi-testicular volume, FSH and FSHB genotype. Cluster 1 contained all men homozygous for G (wildtype) in FSHB c.-211G>T (100%), while Cluster 2 contained most patients carrying a T allele (>96.6%). In analyses of sub-cohorts A/B, two clusters each were also formed. Again, the strongest segregation markers between the respective clusters were bi-testicular volume, FSH and FSHB c.-211G>T. Conclusion: With this first unbiased approach for revealing putative subgroups within a heterogenous group of idiopathic infertile men, we did indeed identify distinct patient clusters. Surprisingly, across all diverse phenotypes of infertility, the strongest segregation markers were FSHB c.-211G>T, FSH, and bi-testicular volume. Further, Cohorts A and B were significantly separated by FSHB genotype (wildtype vs. T-allele carriers), which supports the notion of a contributing genetic factor. Consequently, FSHB genotyping should be implemented as diagnostic routine in patients with idiopathic infertility.